Fiscal neutrality toward economic growth: analysis of a taxation principle - Phelps, Edmund S. (New York: McGraw-Hill, 1965)
The book examines fiscal neutrality toward economic growth. Topics covered include the nature and signfiicance of gevernment controls over growth; fiscal neutrality toward growth in a Barter economy; fiscal neutrality toward growth in a Monetary economy.
Bibliography: p. 107-109.
obn 23/01/2019
Loans
Keywords: Fiscal policy; Economic policy; Economic growth